Design And Analysis of Seed Sowing Mechanism for Agriculture ROBOT - A Nageswara Rao, B Chaitanya, Dr. S Pichi Reddy, N Raju, B Udaya Lakshmi, B D I Premkumar (International Journal of Modern Agriculture, 2021)
Agriculture is the primary source of income for nearly 70% of Indians. As a result, India's agricultural system should be advanced in order to reduce farmers' efforts. Crop sowing, weeding, cutting, pesticide spraying, and other operations are all conducted in the agriculture sector. Primary and significant operation is seed sowing in agriculture field. Seed sowing work was repetitive task, which required more human effort. Hence the scope of developing machinery to reduce the efforts of farmers is very necessary. Present study is an attempt to make the design and development of Agriculture Robot for seed sowing application. Agriculture Robot consists of seed sowing mechanism and robot. A four blade rotor van is key component in seed sowing mechanism, with the help of motor rotor drive shaft. Rotor van blade is design and perform analysis with different materials to get deflections and stresses. Entire model is made by computer aided design then develop the model. Seed sowing mechanism and robot is interface properly. As it moves down the aisle, the robot uses its keen sensors to level itself with the slots. When the robot reaches the trough, it send signal to activates motor with a rotor. The distance travelled by the robot is calculated using data from the wheel encoder. This knowledge is help to trigger the seed sowing mechanism, allowing the crop's inter-seeding travel to be reduced. Proposed seed sowing agriculture robot will useful to farmers to solve agriculture problems.